2016
DOI: 10.4116/jaqua.55.1
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary tephrostratigraphy of underground sediments in the middle west part of Aizu Basin, Fukushima, northeast Japan

Abstract: 東北日本弧南部,福島県会津坂下町で得た 3 本のボーリングコアからテフラを検出し,これら の認定を行い会津盆地中西部地下のテフラ層序を確立した.また放射性炭素年代測定も実施し, それらの結果と合わせて盆地堆積物の年代と堆積速度を求めた.地下約 100 m 以浅の堆積物は シルト・泥炭・砂を主体とし,ところにより礫層やテフラを挟む.認定したテフラは上位から Nm-NM (5.4 ka) ,AT (30 ka) ,DKP (55~66 ka) ,Nm-KN,Ag-OK (<85.1 ka) ,TG (129 ka) , Sn-MT (180~260 ka) である.最長コアから得た堆積速度は,地表/DKP 間で 0.46~0.55 m/ kyrs, DKP/TG 間で 0.19~0.23 m/kyrs である. キーワード:ボーリングコア,会津盆地,姶良 Tn テフラ,大山倉吉テフラ,沼沢金山テフラ, 田頭テフラ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The first layer, TKN1080 (Nagahashi et al, 2007;Kimura et al, 2015), is recorded in the Takano Formation (Fig. 1), whilst a second layer is reported in a borehole 600 km north-east of Daisen in Naka-iwata, Aizu-bange town (Suzuki et al, 2016) (Fig. 1).…”
Section: Pre-at Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The first layer, TKN1080 (Nagahashi et al, 2007;Kimura et al, 2015), is recorded in the Takano Formation (Fig. 1), whilst a second layer is reported in a borehole 600 km north-east of Daisen in Naka-iwata, Aizu-bange town (Suzuki et al, 2016) (Fig. 1).…”
Section: Pre-at Activitymentioning
confidence: 99%
“…Distally the SAN1 marine tephra glass compositions following Ikehara et al (2015), and new glass data from the equivalent layers in Sea of Japan cores (GH89-2-27 and GH89-2-25) ( Table 4; Supplementary material). Finally the SG06 data is compared to glass data of a two distal DKP candidates; (1) TKN1080 from the Takano formation (Nagahashi et al, 2007) and (2) a distal layer (30.08-30.12m) recovered from borehole AB12-2 in Naka-iwata, Aizu-bange town 600 km north of Daisen volcano (Suzuki et al, 2016; Table 4). All ages reported that are outside the 14 C timeframe are provided in ka with 2σ errors (equivalent to 95.4% probability range).…”
Section: Figurementioning
confidence: 99%
“…In order to reconstruct the shallow subsurface geological structure of the Aizu Basin, we first analyzed four sedimentary core samples (GS-AZU-1, GS-SOK-1, GS-NT-1, and AB-12-2 shown in Figure 1) that were drilled in the basin [27][28][29]. The depths of each core range from 99.95 to 130.00 m. Additionally, lithofacies data from 790 boring and snow melting well logs were collected.…”
Section: Analysis Of Shallow Subsurface Geological Structurementioning
confidence: 99%
“…Occasional peat layers are also observed in some cores. The age of the core sediments was determined based on the chronological analyses including tephras (volcanic ashes and pyroclastic flow sediments) and radiocarbon dating [27][28][29]. All strata consist of Quaternary systems including the middle Pleistocene, upper Pleistocene, and Holocene.…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation